Scleral buckling for primary rhegmatogenous retinal detachment using noncontact wide-angle viewing system with a cannula-based 25 G chandelier endoilluminator - Imai, Hisanori (Clin Ophthalmol, 2015)
PURPOSE: The aim of this study is to report the result of scleral buckling (SB) using a combination of a noncontact wide-angle viewing system and a cannula-based 25 G chandelier endoilluminator. METHODS: Retrospective analyses of the medical records of 79 eyes of 79 patients with primary uncomplicated rhegmatogenous retinal detachments who had underwent SB using a combination of a noncontact wide-angle viewing system and a chandelier endoilluminator were performed. RESULTS: There were 50 men and 29 women. The mean ± standard deviation age was 43.7±16.0 years. Their preoperative best-corrected visual acuity (BCVA) was 0.31±0.65 logMAR units. The final BCVA was 0.10±0.31 logMAR units, which was significantly better than the preoperative BCVA (P<0.01). The initial and final anatomical success rates were 92.4% and 100%, respectively. Backward logistic multiple regression analysis revealed no relationship between explanatory variables and the primary anatomic success (P=0.104). CONCLUSION: SB using a combination of a noncontact wide-angle viewing system and a chandelier endoilluminator is a modified new technique and may be a valid option for the management of rhegmatogenous retinal detachments.